Assessment of Heavy Metal Contamination in Soils of the Kenana Industrial Area Compared to Control Sites and WHO Standards in Dry and Wet Seasons - Ahmed Kabbashi Ahmed Talab; Bakheit Mustafa Mohammed salih (White Nile Journal for Studies and Research, 2026)
This study investigates the levels of selected heavy metals—Iron (Fe), Copper (Cu), Lead (Pb), Chromium (Cr), Manganese (Mn), and Zinc (Zn)—in soils collected from the Kenana industrial area and nearby control sites during both dry and wet seasons. Soil samples were collected at depths of 0 to 20 cm and distances of 300 to 500 cm, and analyzed using Atomic Absorption Spectrophotometry (AAS). Results showed that Chromium concentrations in the study area reached up to 142.5 ppm in the wet season, significantly exceeding the WHO permissible limit of 100 ppm. Copper levels also exceeded the standard of 36 ppm, with values averaging 41.1 ppm in the dry season and 43.2 ppm in the wet season. In contrast, other metals—Iron (average 22.9 ppm), Lead (27.6 ppm), Manganese (794 ppm), and Zinc (40.6 ppm)—remained within acceptable ranges in most samples. Cadmium (Cd) was not detected in any sample. Seasonal variation was evident, with higher accumulation generally occurring in the wet season due to increased metal mobility and leaching. These findings highlight significant environmental and public health concerns related to industrial activities and emphasize the need for regular monitoring and soil management strategie.